Option B:
is the new equation
Explanation:
The given equation is ![$y=-\sqrt[3]{x}$](https://tex.z-dn.net/?f=%24y%3D-%5Csqrt%5B3%5D%7Bx%7D%24)
We need to find the new graph which is shifted 7 units up and 4 units right.
First, we shall shift the graph 7 units up.
The general formula to shift the graph b units up is given by
![y=f(x)+b](https://tex.z-dn.net/?f=y%3Df%28x%29%2Bb)
Thus, to shift the graph 7 units up, let us substitute
and
in the general formula, we have,
![y=$-\sqrt[3]{x}$+7](https://tex.z-dn.net/?f=y%3D%24-%5Csqrt%5B3%5D%7Bx%7D%24%2B7)
Now, we shall shift the graph 4 units right.
The general formula to shift the graph b units right is given by
![y=f(x-b)](https://tex.z-dn.net/?f=y%3Df%28x-b%29)
Thus, to shift the graph 4 units right, let us substitute
and
in the above equation, we have,
![$y=-\sqrt[3]{x-4}+7$](https://tex.z-dn.net/?f=%24y%3D-%5Csqrt%5B3%5D%7Bx-4%7D%2B7%24)
Therefore, the new equation is ![$y=-\sqrt[3]{x-4}+7$](https://tex.z-dn.net/?f=%24y%3D-%5Csqrt%5B3%5D%7Bx-4%7D%2B7%24)
Therefore, Option B is the correct answer.